(untitled) (SALAM Digest: Syariah and Law Undergraduate Symposium, 2024)
Digital transaction is the process of exchanging goods, services, or information through electronic means, such as the internet, mobile devices, or block chain. Digital transaction has significant implications for the Islamic finance and economy sector in Malaysia, especially from the Shariah perspective. Shariah is the divine law of Islam that governs all aspects of life, including economic, social, and ethical matters. Shariah aims to achieve justice, fairness, and welfare for all parties involved in any transaction or contract, as well as to attain the ultimate goal of human happiness and success in this world and the hereafter. This paper examines and evaluates the legal and ethical implications of digital transaction from the Shariah perspective in Malaysia. The paper adopts a qualitative and descriptive approach, using various sources of data, such as the laws and regulations, the Shariah principles and rules, the Shariah guidance and rulings, and the web search results, to analyse and discuss the issues and challenges, as well as the solutions, of digital transaction in Malaysia. The paper finds that digital transaction in Malaysia is governed by various laws and regulations, as well as the Shariah principles and rules, that aim to ensure the validity, permissibility, and security of digital transaction, as well as to protect the rights and interests of the parties involved. The paper also finds that digital transaction in Malaysia poses various ethical challenges and opportunities for the Islamic finance and economy sector, which require the parties involved in digital transaction to exercise their moral judgment and responsibility, as well as to consult the relevant authorities and experts, in order to ensure the compliance and alignment with the Shariah principles and values, as well as the relevant laws and regulations, in digital transaction. The paper concludes that digital transaction in Malaysia is a phenomenon that offers various opportunities and challenges for the development and innovation of the Islamic finance and economy sector in Malaysia, and that it is crucial to examine and evaluate the legal and ethical implications of digital transaction from the Shariah perspective in Malaysia, and to ensure the optimal outcomes and benefits for the Islamic finance and economy sector in Malaysia, and for the society at large.